Comparison of metabolic kinetics during high and low solids anaerobic digestion of fecal sludge. Issue 4 (23rd January 2022) - Kinyua, Maureen; Stuart, Kara
Abstract: High solids anaerobic digestion (HS‐AD) is an attractive energy‐producing technology; however, high total solids (TS) content may inhibit methanogens due to high volatile fatty acid (VFA) and total ammonia nitrogen concentrations. The objective of this paper is to quantify rate‐limiting metabolic kinetic parameters to determine the influence of TS content during anaerobic digestion of fecal sludge. Two TS content: 11% and 17% microcosms were analyzed. Good performance was observed in both systems, with volatile solid (VS) removal greater than 50%, CH4 yield between 0.44 and 0.56 m 3 CH4 /g VS added and cumulative CH4 production between 1.78 and 2.03 m 3 CH4 /m 3 digester‐day. At 11% TS VFA consumption and VS removal had a positive correlation to CH4 production while the 17% TS microcosm had a negative correlation with both. This is the first study to determine the kinetic parameters for hydrolysis, VFA consumption, and methanogenesis during digestion of fecal sludge. These kinetic parameters are necessary in the design and operation of anaerobic digestion systems treating fecal sludge. Abstract : Summary of study objective and approach